Pembingkaian Berita Isu Pembangunan Wisata Premium Komodo pada Mongabay.co.id dan Greeners.co : Indonesia - Anggita Putri; Wininda Qusnul (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
In October 2020, the Indonesian people were shocked by the appearance of a photo on the @kawanbaikkomodo twitter account containing a truck being blocked by a Komodo dragon. This photo is related to the development of premium Komodo tourism on Rinca Island. Environmental problems in Indonesia often occur every year and even continue to increase. Mass media is considered effective and has a big influence in increasing public awareness of the environment. As media that are concerned with environmental issues, Mongabay.co.id and Greeners.co also report on the issue of Komodo premium tourism development. This study aims to find out how Mongabay.co.id and Greeners.co frame the issue of komodo tourism development and find out the factors that influence the framing of the two media. This study uses a descriptive qualitative approach with the framing analysis method of the Robert N. Entman model. The results show that Mongabay.co.id focuses on reporting on the impact of development on the environment, animals and society. Meanwhile, Greeners.co focused on reporting on the development process which was deemed not to pay attention to the Komodo dragon. There are two factors that most influence the two media in determining framing, namely the level of media routine and ideology.